Learning Problems in Children With Mild Intellectual Disability - Keskinova, Angelka; Ajdinski, Goran (The Association for the development of science, engineering and education, 2018)
School failure is one of the more complex, more difficult and unfor-tunately frequent problem that modern school meets. Many factors can cause school failure, such as: child development characteristics, family and school-originated factors. The purpose of the research is analysis of the specific learning problems in students with a mild intellectual disability. For our research we used ACADIA test, which contains 13 subtests for assessing the overall individual functioning. The research involved 144 students. We divided the sample into two groups, children with intellectual disability (our target group) and control group. We found that generally all students with the intellectual disability have special learning problems. According to individual subtests analysis we concluded that the ability for visual association is best developed among these students while on the subtest for auditory memory they achieved worse results. With the analysis of the control group we found that 13.75% of the students have special learning problems.
Keywords: Learning problems; Mild intellectual disability; ACADIA test; development abilities